Non-standard employment and wage growth in Australia - Lass, Inga; Wooden, Mark (My University, 2020)
Using data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey, and after restricting attention to employees, we observe an increase over time in the non-standard employment share, all of which is concentrated in the period since 2009. Further, we find clear evidence that employees in non-standard forms of employment have experienced relatively low rates of growth in hourly wages when compared with permanent full-time employees. Nevertheless, decomposition analysis suggests that changes in workforce composition by employment type have had a very small (and insignificant) impact on the overall rate of wage growth in recent years.
Australian Economic Review
Keywords: Labour market